STUDI PERBANDINGAN MODEL PERHITUNGAN LABA ANTARA PEGADAIAN SYARIAH DENGAN PEGADAIAN KONVENSIONAL - LUGITO, ARMAN (Jurnal Akuntansi AKUNESA, 2013)
The objective of this study is to compare profit model Sharia pawnshop and Konvensionalpawnshop. By using descriptive qualitative research the study portrays the accountingsystem between Sharia and Konvensional pawnshop. The purpose of this study is to knowhow the Sharia and Konvensional pawnshop get the profit with personal accountingsystem. Then, by this study to hope give information for people get decision and tochoose the pawnshop. Finally, between Sharia and Konvensional pawnshop, Sharia is notuse pay loan method to get profit dan Sharia pawnshop is not use fidusia model to getprofit.Keyword: Profit, Sharia accounting, Konvensional accounting